2009
DOI: 10.1103/physrevb.80.235411
|View full text |Cite
|
Sign up to set email alerts
|

Nernst and Seebeck effects in a graphene nanoribbon

Abstract: The thermoelectric power, including the Nernst and Seebeck effects, in graphene nanoribbon is studied. By using the non-equilibrium Green function combining with the tight-binding Hamiltonian, the Nernst and Seebeck coefficients are obtained. Due to the electron-hole symmetry, the Nernst coefficient is an even function of the Fermi energy while the Seebeck coefficient is an odd function regardless of the magnetic field. In the presence of a strong magnetic field, the Nernst and Seebeck coefficients are almost … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
78
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 44 publications
7
78
0
Order By: Relevance
“…For this favorable technology, the most intrinsic parameter is the Seebeck effect which plays an indispensable role in converting temperature differences directly into electrical voltages [7][8][9]. Although the thermoelectric Seebeck effect was firstly discovered by Thomas Johann Seebeck in 1821 [10], the basic principle for harvesting electricity from a temperature gradient was utilized and developed as the contemporary technology in inorganic semiconductors until the late 1950's [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For this favorable technology, the most intrinsic parameter is the Seebeck effect which plays an indispensable role in converting temperature differences directly into electrical voltages [7][8][9]. Although the thermoelectric Seebeck effect was firstly discovered by Thomas Johann Seebeck in 1821 [10], the basic principle for harvesting electricity from a temperature gradient was utilized and developed as the contemporary technology in inorganic semiconductors until the late 1950's [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18] Because of the quantum confinement effect, graphene and h-BN exhibit very high electrical conductance and Seebeck coefficient. [19][20][21] However, both pristine graphene and pristine h-BN are poor thermoelectric materials because their thermal conductance is also very high. [22][23][24][25] Recently, a novel nanomaterial compounded of graphene and h-BN has been synthesized by the thermal catalytic chemical vapor deposition method.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in section 3.3.3, with regard to the diffusion TEP, the geometry and edge roughness can greatly influence the TE properties of GNRs [7,65,[88][89][90]109]. A dramatic reduction in phonon transport in ZGNR [7] indicates small value for Λ.…”
Section: Phonon-drag Thermopower In Agnrmentioning
confidence: 99%
“…Divari and Kliros [87] have studied TEP of ballistic wide graphene ribbons with aspect ratio (W/L ≥ 3) using linear response theory and the Landauer formalism. Xing et al [88] have studied TEP of GNRs in zero and non-zero magnetic field using non-equilibrium Green's function technique and shown that TEP depends on the chirality of the GNR. The TE properties have also been investigated by solving the electron and phonon transport equations in the nonequilibrium Green's function formalism [7,[89][90][91].…”
Section: Diffusion Thermopower In Agnrmentioning
confidence: 99%